Redesign of Mobility Aids for Spastic Diplegic Cerebral Palsy Children Through Collaboration Among Academics - Medical Devices Industry and User Intitutions - Lobes Herdiman IPM; Susy Susmartini; Taufiq Rochman (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
Cerebral palsy (CP) children are part of the neuro disability spectrum in impaired brain function. The etiological understanding of CP children for primary prevention and early treatment can reduce the effects of damage to brain function. CP children with cerebral diplegia are motor developmental disorders caused by damage to the brain characterized by weakness in the lower limbs heavier than the upper limbs. The walker product is designed through a universal design approach to provide as much as possible mobility to CP children in general. A universal design approach to the walker products through the triple helix collaboration included academic, medical devices industry and user institutions. Three subjects with spastic CP cerebral diplegia children underwent gait training using a walker. Gait performance (continuous walking distance, and maximum and comfortable walking speed) and energy expenditure are measured at the end of the 1-week training session. The purpose of the pediatric walker redesign is to facilitate mobilization of the position of the child's body CP in the anterior and posterior positions. The walker design can be removed from the raft back and forth from both sides at the front. At a certain time, the walker can be positioned behind the user according to the recommendations of some physiotherapy practitioners. This design also facilitates the position of CP children in order to be more precise, reducing double support during ambulation and increasing walking speed. The anterior-posterior walker as an ADVANCED walker for CP children provides the most appropriate position because it provides the best gait pattern and consumes less energy.